Lawrence Hargrave Drive (Sydney, N.S.W. : Roads and Traffic Authority, NSW, 2004)
Lawrence Hargrave Drive, a coastal road north of Wollongong, is one of the most scenic roads in NSW and a major tourist attraction. The 900 metre section of the road between Clifton and Coalcliff is also the highest slope risk section of road in the State, with a long history of rock falls and embankment failure. In August 2003, the State Government announced a major project to upgrade the road.' -- Website.
Contents updated regularly.
Title from home page (viewed on February 23, 2004).
Text and graphics.
Mode of access via the World Wide Web. Available at: http://www.rta.nsw.gov.au/constructionmaintenance/majorconstructionprojectsregional/lawrencehargravedrive/index.html
Selected for archiving
Keywords: Roads and Traffic Authority of NSW; Lawrence Hargrave Drive (N.S.W.)